Consumption and Population Age Structure - Solveig K. Erlandsen; Ragnar Nymoen (Norges Bank, 2004)
In this paper the effects on aggregate consumption of changes in the age distribution of the population are analysed empirically. Economic theories predict that age influences individuals' saving and consumption behaviour. Despite this, age structure effects are rarely controlled for in empirical consumption functions. Our findings suggest that they should. By analysing Norwegian quarterly time series data we find that changes in the age distribution of the population have significant and life cycle consistent effects on aggregate consumption. Furthermore, controlling for age structure effects stabilizes the other parameters of the consumption function and reveals significant real interest rate effects. Simulation experiments show that the numerical effect on the savings rate of age structure changes is substantial when the indirect effects via wealth and income are accounted for.
hdl:11250/2498530
Keywords: C51; C53; E21; J10; 330; consumption; demography; savings; time series models; cointegration